Pharmacokinetics of testosterone cream applied to scrotal skin. (23rd March 2017) - Iyer, R.; Mok, S. F.; Savkovic, S.; Turner, L.; Fraser, G.; Desai, R.; Jayadev, V.; Conway, A. J.; Handelsman, D. J.
Summary: Scrotal skin is thin and has high steroid permeability, but the pharmacokinetics of testosterone via the scrotal skin route has not been studied in detail. The aim of this study was to define the pharmacokinetics of testosterone delivered via the scrotal skin route. The study was a single‐center, three‐phase cross‐over pharmacokinetic study of three single doses (12.5, 25, 50 mg) of testosterone cream administered in random sequence on different days with at least 2 days between doses to healthy eugonadal volunteers with endogenous testosterone suppressed by administration of nandrolone decanoate. Serum testosterone, DHT and estradiol concentrations were measured by liquid chromatograpy, mass spectrometry in extracts of serum taken before and for 16 h after administration of each of the three doses of testosterone cream to the scrotal skin. Testosterone administration onto the scrotal skin produced a swift (peak 1.9–2.8 h), dose‐dependent ( p < 0.0001) increase in serum testosterone with the 25 mg dose maintaining physiological levels for 16 h. Serum DHT displayed a time‐ ( p < 0.0001), but not dose‐dependent, increase in concentration reaching a peak concentration of 1.2 ng/mL (4.1 nm ) at 4.9 h which was delayed by 2 h after peak serum testosterone. There were no significant changes in serum estradiol over time after testosterone administration. We conclude that testosterone administration to scrotal skin is well tolerated and produces dose‐dependent peak serum testosterone concentration with a much lower dose relative to the non‐scrotal transdermal route.